Pengaruh Mata Diklat Produktif Akuntansi dan Pengalaman Prakerin Terhadap Kesiapan Kerja dengan Variabel Moderasi Efikasi Diri - Aillin Syandianingrum; Eko Wahjudi (Jurnal Pendidikan Akuntansi (JPAK), 2021)
Vocational High School has the main objective of creating human resources who are ready to work in accordance with their field of expertise. It is hoped that SMK graduates will be well absorbed into employment and be able to reduce unemployment in Indonesia. In fact, the data listed in the Indonesian Central Statistics Agency as of February 2018-2020 shows that SMK graduates have the highest unemployment rate among other education levels, namely 8.94%. Reinforced by data from preliminary observations on the graduates of SMKS Rajasa Surabaya, the accounting expertise program shows that during the last three years there are more than 50% of students who do not have the readiness to work. Factors that are thought to improve student work readiness are productive accounting training course, internship experience, and self-efficacy. The purpose of this quantitative research is to test self-efficacy to moderate the effect of accounting productive subject and internship experience on job readiness. The population in this study were students of class XII Accounting at SMKS Rajasa Surabaya in the academic year 2020/2021, totaling 50 students. Sampling using saturated sampling technique. Data were collected using documentation techniques and questionnaires that have been tested for validity and reliability. The research hypothesis testing was carried out using Structural Equation Modeling. The results of the descriptive analysis showed that the students accounting productive subject, the level of work readiness, and self-efficacy of the students were in good categories, and the students' practical internship experiences were in the moderate category. The results of hypothesis testing show that there is a significant positive effect of accounting productive subject and internship experience on work readiness, and self-efficacy is able to strengthen the effect of accounting productive subject and internship experience on student work readiness.